Pengembangan Media Pembelajaran Berbasis Multimedia Pada Mata Kuliah Kompetensi Pembelajaran Pokok Materi Keterampilan Dasar Mengajar - Gilang Mawardi; Tuti Iriani; Daryati Daryati (LPPM Universitas Negeri Jakarta, 2019)
This research is a type of research and development that aims to produce products in the form of multimedia powerpoint-based learning media in Learning Competency courses. This development research is a Research and Development research method with the 4D (four-D) model. This research is basically done through four main stages, namely define process, design process, develop process, and disseminate process. However, the research only reaches the stage of the development process. This study uses a questionnaire as a tool to test the feasibility of the media through the validation of media experts and material experts. The results of development are multimedia powerpoint-based learning media products. Assessments by material expert lecturers get scores 4,27 categorized as